Correlation between microbial communities and flavor compounds during the fifth and sixth rounds of sauce-flavor baijiu fermentation. (December 2021) - Wang, Wenhua; Xu, Youqiang; Huang, Huiqin; Pang, Zemin; Fu, Zhilei; Niu, Jialiang; Zhang, Chengnan; Li, Weiwei; Li, Xiuting; Sun, Baoguo
Graphical abstract: Highlights: Lactobacillus and Issatchenkia are dominant genera in the fermentation process. Ester compounds and p -cresol contribute to different flavors of fermented products. Correlation analysis indicates the relationships of flavor chemicals with microbes. Bacterial and fungal synthetic pathways of p -cresol are firstly proposed. Abstract: Sauce-flavor baijiu is a representative of Chinese traditional fermented baijiu using grains as the raw materials through the co-fermentation of microorganisms. The whole manufacturing process includes 7 times of distillation and generates 7 kinds of base baijius. The final product is a mixture of the 7 kinds of base baijius. Thus the base baijius greatly affect the quality of the final product. The quality of the base baijiu obtained by the sixth distillation is obviously poorer than that of the fifth one. However, the reason is still unclear and limits the quality control of baijiu fermentation. In this study, the flavor substances and microbiota in the up, middle and bottom layers of fermented grains in the fifth and sixth rounds were compared. Some flavor esters showed obviously decreased concentrations in the sixth round, including ethyl benzoneacetic acid, ethyl hexanoic acid, ethyl dodecanoic acid, diethyl butanedioic acid, and ethyl 2-hydroxyl-propanoic acid. Meanwhile, an off-flavor p -cresol was detected in the sixth round. Correlation analysis of flavor chemicals and microbiota indicated that fungi in the fifth round played an important role for ester synthesis. Some bacterial and fungal species were both positively correlated with p -cresol synthesis, and the related p -cresol metabolic pathways were proposed for the first time. These results revealed flavor divergences of fermented grains between the fifth and sixth rounds, and will ultimately help to improve baijiu quality.